ANALISIS MANAJEMEN LABA DAN KINERJA KEUANGAN PERUSAHAAN SEBELUM DAN SESUDAH AKUISISI YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2013 – 2015 - Ardillahidayah Ardillahidayah; Hadi Sunaryo (E-JRM : Elektronik Jurnal Riset Manajemen, 2018)
ABSTRACT The purpose of this research is to find out the difference of financial performance whetherit exist or not before and after the acquisition. The sample in this research is a manufacturing company listed on the BEI that made the acquisition in 2013. The data analysis techniques in this research is a different test Paired Samples Test where financial performance seen from profitability ratios, liquidity ratios, and solvency ratios.For further research is expected to conduct research on different types of companies so that can be seen the difference in the results of each - each type of company. Keywords : Acquisition, Financial Performance, Finacial Ratio.